Membangun Generasi Melek Finansial: Edukasi Pengelolaan Keuangan dan Mitigasi Risiko Judi Online IPNU IPPNU Mijen - Kholilatul Khusni; Darma Taujiharrahman; Mesi Herawati; Yeyen Novita; Achmad Nur Alfianto (Yayasan Sagita Akademia Maju, 2026)
This community service program aimed to improve the financial literacy and awareness of online gambling risks among members of IPNU–IPPNU Mijen District. The activity focused on two main aspects: personal financial management, including budgeting, saving, financial planning, and expenditure recording; and mitigation of online gambling risks through education on the economic, social, and psychological impacts of digital gambling activities. The program was implemented in three stages, namely an initial survey to identify participants’ financial literacy levels and understanding of online gambling risks, an interactive workshop involving lectures, discussions, case studies, and practical simulations, and an evaluation through post-tests and reflective discussions. The results indicated a significant improvement in participants’ knowledge and skills regarding personal financial management as well as their awareness of the dangers of online gambling. Participants also demonstrated a stronger commitment to managing their finances responsibly and avoiding risky financial behaviors in the digital environment. This program highlights that structured financial literacy and risk-awareness education can effectively strengthen the financial resilience of young people, although continuous mentoring and follow-up programs remain necessary to ensure sustainable behavioral change.